Sosialisasi Menggunakan Media Sosial Berbasis Digital - Dewi Sri Woelandari; Novita Wahyu Setyawati (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
This activity aims to provide education, knowledge, and Digital-Based Marketing skills by using social media for home industries in order to increase their profits and sales.The method used in this community service activity uses, lectures using power point slides to explain general knowledge to home industry players about how to use Digital-Based Marketing to increase profits and sales for MSME businesses, share experiences by conducting discussions and question and answer sessions, and practice and how to make buyers interested in buying products made by MSME.As a result of this activity, participants came to understand and understood what was explained by the resource persons. This activity aims to provide education, knowledge, and Digital-Based Marketing skills by using social media for home industries in order to increase their profits and sales.The method used in this community service activity uses, lectures using power point slides to explain general knowledge to home industry players about how to use Digital-Based Marketing to increase profits and sales for MSME businesses, share experiences by conducting discussions and question and answer sessions, and practice and how to make buyers interested in buying products made by MSME.As a result of this activity, participants came to understand and understood what was explained by the resource persons.